Perfil demográfico e de morbidade da população idosa atendida nas dependências do pronto-socorro, ambulatórios e enfermarias no HC-Unesp em 1997 - De Rezende, Nicola Oliveira [UNESP]; Yamada, Patrícia Martins [UNESP]; Ruiz, Tânia [UNESP] (My University, 2002)
Being our objective to characterize demographic and morbidity patterns of the 60 years old or more attended at the UNESP Clinic Hospital in 1997 a sample consisting of 482 handbooks has been analyzed in order to evaluate ambulatory attendance, other consisting of 101 handbooks to evaluate first aid clinic demand and statistics from Medical Informatic Center (Centro de Informática da Medicina - CIMED) refering to 2652 internments of such populations this year. Ten and a half per cent from the total of first aid clinic attended patients refers to this old people and the majority (57,4%) lives in Botucatu County. More frequently diagnoses during consultation are Chronic Obstructive Lung Disease (10.1%), Congestive Cardiac Disease (4.7%), Asthma and Cataract (3.1 % for both). Such population is also referred to be 19.8% from the number of all patients attended at the UNESP ambulatories, 65.8% coming from other city in São Paulo State, being in average 69.6 years old and attending 4.5 consultations in average by year. More frequently found diagnoses referred to Essential Primary Hypertension (4.2%), Prostatic Nodular Hyperplasia (4.0%) and Nonspecified Cataract (3.3%). Regarding to internments, they referred to be 18.4% from the number of all interned patients. More frequent diagnoses at internmemt referred to Nonspecified Cataract (12%), Glaucoma (3.0%), Prostatic Nodular Hyperplasia (2.4%) and Limbs Arteriosclerosis (2.3%). Results indicates the existence of an tertiary hospital divided into specialties, also attending morbidity that should be in control into levels of primary and secondary attention.
Demographic and morbidity profile of the elderly cohort evaluated with medical resources in 1997 in the HC-Unesp outpatients, emergency department, and wards
Keywords: Aged people health; Hospitalar morbidity; Morbidity survey